2010
DOI: 10.1016/j.joca.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to change of cartilage morphometry using coronal FLASH, sagittal DESS, and coronal MPR DESS protocols – comparative data from the osteoarthritis initiative (OAI)

Abstract: Objective The Osteoarthritis Initiative (OAI) is targeted at identifying sensitive biomarkers and risk factors of symptomatic knee OA onset and progression. Quantitative cartilage imaging in the OAI relies on validated FLASH sequences that suffer from relatively long acquisition times, and on a near-isotropic double echo steady state (DESS) sequence. We therefore directly compared the sensitivity to cartilage thickness changes and the correlation of these protocols longitudinally. Methods Baseline and 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 28 publications
5
83
1
1
Order By: Relevance
“…9,25,[29][30][31][32] In the present study, joint cartilage was examined using the 3D-DESS sequence on a 3-T MRI scanner, which various studies have shown to be very well suited for this purpose and, therefore, has served as a standard of reference in cartilage imaging in many major preceeding studies. [9][10][11] In addition to visualizing the actual cartilage thickness plus adequate contrasting of the cartilage-bone border, this sequence has the advantage of enabling multiplanar 3D reconstruction, thus allowing detailed evaluation of joint cartilage lesions. 10,11,33 Based on the current development of various cartilage-specific sequences for improving sensitivity, the status of 3-T MRI as an accurate diagnostic tool, especially for grade III and IV cartilage defects, can be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,25,[29][30][31][32] In the present study, joint cartilage was examined using the 3D-DESS sequence on a 3-T MRI scanner, which various studies have shown to be very well suited for this purpose and, therefore, has served as a standard of reference in cartilage imaging in many major preceeding studies. [9][10][11] In addition to visualizing the actual cartilage thickness plus adequate contrasting of the cartilage-bone border, this sequence has the advantage of enabling multiplanar 3D reconstruction, thus allowing detailed evaluation of joint cartilage lesions. 10,11,33 Based on the current development of various cartilage-specific sequences for improving sensitivity, the status of 3-T MRI as an accurate diagnostic tool, especially for grade III and IV cartilage defects, can be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In addition to visualizing the actual cartilage thickness plus adequate contrasting of the cartilage-bone border, this sequence has the advantage of enabling multiplanar 3D reconstruction, thus allowing detailed evaluation of joint cartilage lesions. 10,11,33 Based on the current development of various cartilage-specific sequences for improving sensitivity, the status of 3-T MRI as an accurate diagnostic tool, especially for grade III and IV cartilage defects, can be confirmed. 25,30,[34][35][36] von Engelhardt et al 30 reported a uniform (medial, lateral) distribution of grade I/II defects in 3-T MRI examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FLASH tekniğinin kıkırdak defektinin saptanmasındaki tanısal performansı 2D SE ve 3D GRE teknikleri ile benzer olup diz kıkır-dağının morfolojik değerlendirmesinde kabul edilen görüntüleme tekniklerindendir [41]. Ancak bu tekniğin osteoartrit çalışmalarında zamanla oluşan kıkırdak incelmesi ve hacim kaybının değerlendirilmesinde kullanışsız olduğu gösterilmiştir [42]. Yağ baskılama ile veya su uyarılması ile birlikte kullanılabilir.…”
Section: Spoiled Gradient Recalled Echo Imaging (Spgr)unclassified
“…The iDESS sequence originates from the double-echo steady-state (DESS) technique, [20][21][22][23][24][25][26][27] with the main difference in the order of echo acquisition. Figure 1(a) plots the schematic sequence diagram including the readout gradient waveforms of the DESS sequence.…”
Section: A the Idess Techniquementioning
confidence: 99%